TOKOH DAN LATAR BUDAYA DALAM LA SAISON DE L’OMBRE - Daniel, Yapet; Hasbullah, Hasbullah; latjuba, ade yolanda (JURNAL ILMU BUDAYA, 2016)
The title of this research is “Character and the Cultural setting in La Saison de L’Ombre”. The mainobjective of the research is to idenify and to describe the cultural setting of the novel. The descriptivemethod is applied by means of basic structural theory including setting., character andcharacterisation. The working of the analysis followed the research sequence as follows. The first stepis to identify the social setting and social or cultural from Mulongo clan, Bwele and Bebayadi. Thesecond step will be focused on the identification and the description of the characters in every clan.The third and the final step is to describe the impact of setting on the character’s behaviour andaction. This research has found that the setting had influence on the character’s action and behaviour,The setting has classified and opposed the clan of Mulongo in the mystical belief side and The Bweleand he Bebayedi’s clan in the other side who do not have faith t all in such mystical things.Key words: cultual setting, impact, mystical